Implementation of Nursing Service Operations in Maguindanao Provincial Hospital, Philippines - Ryan Uda; Saidamin Bagolong (Philippine Association of Institutions for Research, Inc., 2023)
With the increasing dimension of medical sciences, nursing care is becoming more and more complex with its management services. This study aimed to evaluate the implementation of Nursing Service Operations in Maguindanao Provincial Hospital in terms of Emergency Room and In-patient services, the processes followed in terms of Triaging, Profiling, Admission, Treatment, and Discharging, and the patients' status such as Admission to Ward and Discharge from Care. The study utilized a descriptive-evaluative method using a researcher-made survey questionnaire to 255 respondents comprising 107 hospital staff and 148 discharged patients. Data were analyzed using the weighted mean. Results revealed that Emergency Room (ER) and In-patient services were highly implemented. There was a very high implementation process for nursing services for triaging, profiling, treatment, and discharge, except for a high admission process. Also, the patient's status regarding admission to the ward for emergency room services was high, while discharge from care for in-patient services was moderate. Regarding problems encountered, it was revealed that the MPH needed more staffed nurses, cultural health beliefs, language barriers, lack of continuous education, delayed salary, etc. Hence, the Maguindanao Provincial Hospital adhered to the guidelines in the DOH Administrative Order 2012-0012; however, certain provisions must be complied with to deliver emergency room and in-patient services effectively and efficiently.